Total thyroidectomy vs completion thyroidectomy for thyroid nodules with indeterminate cytology/follicular proliferation: a single-centre experience - Giuseppe Sena; Gaetano Gallo; Nadia Innaro; Noemi Laquatra; Martina Tolone; Rosario Sacco; Giuseppe Sammarco (BMC Surgery, 2019)
Abstract Background Despite total thyroidectomy (TT) is the most practiced procedure for a preoperatively diagnosed neoplastic lesion, according to the ATA guidelines, many surgeons perform completion thyroidectomy (CT) after hemithyroidectomy for patients with preoperative follicular proliferation/indeterminate cytology who are diagnosed with malignancy. CT has a higher complication rate than the primary procedure. The primary endpoint of our study is to compare the morbidity rate after CT with that after primary TT in patients with follicular proliferation/indeterminate cytology. Methods We retrospectively reviewed 237 patients who underwent thyroid surgery from 2009 to 2018 at our institution. We recruited only patients with follicular proliferation/indeterminate cytology and excluded those undergoing lymphadenectomies and thyroidectomies for benign pathology and staged thyroidectomies after intraoperative documentation of a RLN lesion. One hundred eighty-six of these patients underwent TT, and fifty-one underwent CT for the detection of differentiated thyroid cancer at the histological exam. Results No differences were found in the total complication rates between the two groups (OR 0,76, 95% CI 0.35–1.65, P = 0.49). We did not find any significant differences in the subgroup analysis. In particular, no significant differences were identified for transient hypocalcaemia (OR 1.17, 95% CI 0.44–3.11; P = 0,74), permanent hypocalcaemia (OR 1.04, 95% CI 0.21–5.18; P = 0,95), transient unilateral recurrent laryngeal nerve palsy (OR 0.78, 95% CI 0.21–2.81; P = 0,16), permanent unilateral recurrent laryngeal nerve palsy (OR 1.48, 95% CI 0.28–7.85; P = 0,61), and haematoma (OR 1,84, 95% CI 0,16-20,71; P = 0,61). Conclusions CT following hemithyroidectomy can be performed with acceptable morbidity in patients with thyroid nodules with preoperative indeterminate cytology/follicular proliferation.